Growth, anatomy, quality and yield of wild ginger (Siphonochilus aethiopicus) in response to nitrogen nutrition, fertigation frequency and growing medium - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (MSc (Plant Production))--University of Pretoria, 2004.